Resmetirom: A Breakthrough in the Treatment of Metabolic Dysfunction–Associated Steatotic Liver Disease (MASLD) - Laiba Shakeel; Ayesha Shaukat; Aymar Akilimali (Health Science Reports, 2025)
ABSTRACT Background and Aims Metabolic dysfunction–associated steatotic liver disease (MASLD), previously referred to as non‐alcoholic fatty liver disease (NAFLD), has become the most prevalent chronic liver disease worldwide. Its increasing incidence is closely linked with rising rates of obesity, Type 2 diabetes mellitus (T2DM), and metabolic syndrome. MASLD includes a spectrum of liver pathologies such as fibrosis, cirrhosis, and metabolic dysfunction–associated steatohepatitis (MASH). This review explores diagnostic advancements and therapeutic developments, focusing on Resmetirom, a selective thyroid hormone receptor‐beta (THR‐β) agonist, as a novel pharmacologic intervention. Methods The review draws upon current literature, clinical guidelines, and data from pivotal randomized controlled trials to evaluate the diagnostic criteria, non‐invasive assessment tools, lifestyle recommendations, and emerging pharmacotherapy for MASLD and MASH, focusing on Resmetirom. Results Resmetirom has demonstrated significant efficacy in reducing hepatic fat content and improving markers of liver fibrosis in patients with noncirrhotic MASH and fibrosis stages F2–F3. Clinical trials showed improved liver histology, lipid profiles, and MASH resolution without fibrosis progression. Despite its promising profile, gastrointestinal side effects and gallstone‐related complications have been observed. Long‐term safety and outcomes related to cirrhosis or hepatocellular carcinoma prevention remain under investigation. Conclusion MASLD is a significant public health concern driven by metabolic dysfunction. While lifestyle changes remain central to management, Resmetirom offers a promising pharmacological option for patients with moderate to advanced MASH. Further long‐term studies are needed to fully establish its safety, effectiveness, and role in preventing advanced liver disease.